Particle Size Distribution and Mineral Analysis of Sediments in Nepalese Hydropower Plant: A Case Study of Jhimruk Hydropower Plant - Neopane, Hari Prasad; Sujakhu, Surendra (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Hydro energy is considered as one of the most economically feasible renewable energy for Nepal. In spite of huge hydropower potential in Nepal, only about 2 % of economically feasible hydropower has been extracted at present. Huge sediment transport has not only caused problem in operation and maintenance of Hydro-Power Plant (HPP), but also reduced hydraulic efficiency of the system. Sediment erosion is one of the most challenging circumstances for hydro energy development in Nepal. Particle size and mineral content of the sediment are the two important sediment parameters to define erosion potential of sediment. In this paper, Particle Size Distribution (PSD) analysis and mineral analysis of sediment samples from two different locations of Jhimruk HPP was carried out to report PSD, mineral content and their variation at different sampling locations. Sieve analysis method was used for PSD analysis which revealed that sediment size range of 0.1 mm to 0.2 mm is critical in terms of sediment erosion. And particle count method was used for mineral analysis which indicated quartz to be the predominant mineral in river sediment. It was also found that mineral content varies as the sediment flows from headwork to downstream.